2017
DOI: 10.1093/jnci/djx232
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of Clinical Benefit of Cancer Drugs Approved by the US Food and Drug Administration

Abstract: The number of trials meeting the ESMO-MCBS threshold for clinical benefit has improved over time. However, fewer than half of RCTs supporting FDA approval meet the threshold for clinically meaningful benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
58
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 26 publications
7
58
1
Order By: Relevance
“…New drugs that lower the risk of side effects of chemotherapy have also been developed (DeVita and Chu 2008). The majority of new drugs, however, are approved for advanced-stage cancers and not for first-line therapy (Tibau et al 2018).…”
Section: Measuring Innovation In Cancer Treatmentmentioning
confidence: 99%
“…New drugs that lower the risk of side effects of chemotherapy have also been developed (DeVita and Chu 2008). The majority of new drugs, however, are approved for advanced-stage cancers and not for first-line therapy (Tibau et al 2018).…”
Section: Measuring Innovation In Cancer Treatmentmentioning
confidence: 99%
“…The relevant endpoint for cancer therapy is its impact on overall survival, or in some cases, progression free survival of a cancer patient. Despite some isolated examples of success with inhibitors of HER2, EGFR, BCR/ABL, or ALK kinases, the inconvenient truth from numerous clinical trials tells us that the success of inhibitors of tyrosine or serine/threonine kinases in achieving clinically relevant endpoints is poor . In all listed cases, very potent and selective tyrosine kinase inhibitors (TKIs) have been developed and they mostly show efficient target inhibition, and in many cases initial therapeutic responses, but only BCR/ABL targeting in CML by first‐ and second‐generation TKIs results routinely in patient cure .…”
Section: Introductionmentioning
confidence: 99%
“…Using both the ESMO-MCBS and a modified version adapted for Health Technology Assessment (HTA) [12], an analysis of 5 years (2011-2016) of EMA cancer drug approvals showed that 89 and 79% of therapies did not meet the MCBS or modified threshold respectively [13]. A USA analysis, using the ESMO-MCBS threshold, showed that over the period of 2006-2016, only 43.8% of randomized controlled trials supporting FDA approvals for new cancer drugs met the MCB threshold [14].…”
Section: Clinical Benefitsmentioning
confidence: 99%